Le Capital Immatériel : Evaluation Et Importance Cas Des Entreprises Marocaines Cotées En Bourse - Omar Taouab; Lotfi Benazzou; Aziz Babounia (European Scientific Journal, ESJ, 2016)
Currently, we live in an economy that has changed considerably since the 1990s. This is the time where the economies have moved from the industrial to the information age. For about a decade, companies have switched to the immaterial economy in addition to the physical value (fixed assets: buildings, workshops, computers, vehicles, etc.) and the cash value (cash, receivables, etc.).There is a gaseous value, which is the intangible capital. This new notable concept is the subject of this research, which is to calculate the intangible capital of a sample of listed Moroccan companies, according to an approximate approach, based on publicly available data on Casablanca Stock Exchange website. The purpose of this research is to answer the following questions: What is intellectual capital? What are the components of intangible capital? And what is the weight of intangible capital in Moroccan companies?